Symptom Persistence in a Community Cohort of Women with Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS): 3, 6, 9, and 12 month follow up from the RICE Cohort - Suskind, Anne M. (Int Urogynecol J, 2014)
INTRODUCTION AND HYPOTHESIS: The persistence of interstitial cystitis/bladder pain syndrome (IC/BPS) symptoms has been described in women seeking medical care. The purpose of this study was to determine whether symptoms persist among a population-based sample of women. METHODS: A probability sample of U.S. women was identified through a two-stage telephone screening process using the RICE high-sensitivity case definition. A randomly-selected subgroup (n=508) was enrolled in a longitudinal study and interviewed about their symptoms at baseline, 3, 6, 9, and 12 months. Bivariate and multivariate linear regression analyses determined predictors of persistence of symptoms over the four waves. RESULTS: A total of 436 women with a mean age of 47.5 years responding to all waves were included in the analysis. Forty-one percent met the RICE high sensitivity case definition at baseline and in all four waves; an additional 21% met the definition at baseline and in three waves. Women with a college degree (+12% vs. no college, p=0.02) and who were younger (−5% per decade of age, p<0.01) had higher chances of symptom persistence at each wave. Scoring one standard deviation higher on the continuity of symptoms and the O’Leary Sant Interstitial Cystitis Symptom index increased the chances of symptom persistence by 4% and 2 %, respectively (both p’s<0.01). CONCLUSIONS: The majority of women demonstrated symptom persistence across at least three of four waves over 12 months. These women tended to be younger, college-educated, and to have reported a history of greater continuity of symptoms and higher severity of symptoms at baseline.